Song of Exile - Enslen, Joshua Alma (Purdue University Press, 2022)
Song of Exile: A Cultural History of Brazil’s Most Popular Poem, 1846–2018 is the first comprehensive study of the influence of Antônio Gonçalves Dias’s “Canção do exílio.” Written in Coimbra, Portugal, in 1843 by a homesick student longing for Brazil, “Song of Exile” has inspired thousands of parodies and pastiches, and new variations continue to appear to this day. Every generation of Brazilian writers has adapted the poem’s Romantic verses to glorify the wonders of the nation or to criticize it via parody, exposing a litany of issues that have plagued the country’s progress over the years. Based on a core of five hundred texts painstakingly gathered over a five-year span, this book catalogs the networks of the poem’s reinvention as pastiche and parody in Brazilian print culture from nineteenth-century periodicals to new media. Mapping the reoccurrences of the original’s keywords and phrases over time, the book uncovers how the poem has been used by successive generations to write and rewrite the nation’s history. This process of reinvention has guaranteed the permanency of “Song of Exile” in Brazilian culture, making it not only the nation’s most popular poem, but one of the most imitated in the world.